Pembentukan Kelas Remaja untuk Mencegah Pernikahan Dini di Desa Sisik Lombok Tengah - Lalu Sulaiman; Anjar Pranggawan Azhari (IKIP PGRI Bojonegoro, 2021)
ABSTRACTEarly marriage rates in Central Lombok district was still very high (55.83%). The cause of this condition is due to various factors, as well as socio-cultural factors, economic factors and educational factors. The government recognize that early marriage is one of the risk factor for high maternal mortality rates. Many attempts had been done, but the result was unsatisfactory. Therefore the author tries to make efforts to empower youth through the formation of